Recent pharmacological management of oral bleeding in hemophilic patient - Monica Widyawati Setiawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Hemophilia is a hereditary bleeding disorder that can increase the risk of disease in oral cavity. Sometimes hemophilia is not always established already in a patient. The lack of awareness of hemophilia presence can cause serious problem. Purpose: The purpose of this review is to explain about dental bleeding manifestation and management in hemophilic patient. Reviews: Hemophilia can be manifested as dental bleeding that cannot stop spontaneously. It should be treated with factor VIIII either by giving whole blood, fresh plasma, fresh frozen plasma, cryoprecipitate, and factor VIII concentrate. Factor VIII dose for hemophilia treatment can be calculated based on factor VIII present in hemophilia patient’s body. Factor VIII can also be given as prophylaxis to prevent bleeding. Complications that can be caused by factor VIII replacement therapy are the presence of factor VIII inhibitor and transfusion related diseases. Treatment of dental bleeding due to hemophilia consists of factor replacement therapy and supportive therapy. Conclusion: Treatment of dental bleeding due to hemophilia consists of factor replacement therapy and supportive therapy. There are complications that can happen due to factor VIII replacement therapy that should be considered and anticipated.Latar belakang: Hemofilia adalah kelainan pembekuan darah yang diturunkan. Hemophilia dapat meningkatkan resiko penyakit rongga mulut. Hemofilia tidak selalu sudah terdiagnosa saat penderita melakukan kunjungan ke dokter gigi. Kurangnya kewaspadaan akan adanya hemofilia dapat menyebabkan masalah serius. Tujuan: Tujuan dari kajian pustaka ini adalah memaparkan tentang manifestasi dan penanganan perdarahan gigi pada penderita hemofilia. Tinjauan pustaka: hemofilia dapat bermanifestasi sebagai perdarahan gigi yang tidak dapat berhenti secara spontan. Pada keadaan perdarahan tersebut, pemberian faktor VIII yang diberikan sebagai whole blood, fresh plasma, fresh frozen plasma, cryoprecipitate, dan konsentrat faktor VIII. Dosis faktor VIII sebagai terapi hemofilia dapat dihitung berdasarkan kadar faktor VIII yang terdapat dalam tubuh penderita hemofilia. Faktor VIII juga dapat diberikan sebagai terapi profilaksis untuk mencegah perdarahan. Komplikasi yang dapat terjadi pada pemberian factor VIII replacement therapy adalah timbulnya inhibitor faktor VIII dan penyakit yang terkait transfusi. Terapi perdarahan gigi pada penderita hemofilia terdiri dari factor replacement therapy dan terapi suportif. Kesimpulan: Terapi perdarahan gigi pada penderita hemofilia terdiri dari factor replacement therapy dan terapi suportif. Komplikasi factor VIII replacement therapy harus diwaspadai dan ditatalaksana dengan baik.